Molecular Aspects of Botulinum Neurotoxin 2014
DOI: 10.1007/978-1-4614-9454-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Transport of Botulinum Neurotoxins

Abstract: Botulinum neurotoxin (BoNT) is a potent toxin, which blocks the neurotransmitter release at neuromuscular junctions. BoNT can be acquired from the digestive tract (food-borne botulism, Clostridium botulinum intestinal colonization), respiratory tract (inhalational botulism), or wound (wound botulism). BoNT associates to nontoxic proteins (ANTPs), which have a main role in toxin protection against acidic pH and proteases, especially in the gastrointestinal tract. BoNT, which enters through the digestive or resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 176 publications
(171 reference statements)
0
10
0
Order By: Relevance
“…Minimum amounts of fluorescent HCcB yielding detectable signal in intestinal tissues were around 10 μg per intestinal loop (Fig. Moreover, it has to be taken into account that BoNT/B is less active than BoNT/A, about 10-fold less (Foran et al, 2003;Rasetti-Escargueil et al, 2009), and that only a low toxin fraction passes through the intestinal barrier based on in vivo experiments (reviewed in Popoff and Connan, 2014), therefore justifying the amounts used in this study. We selected to use higher amounts (100 μg/intestinal loop) to more efficiently visualize the cells mediating toxin trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Minimum amounts of fluorescent HCcB yielding detectable signal in intestinal tissues were around 10 μg per intestinal loop (Fig. Moreover, it has to be taken into account that BoNT/B is less active than BoNT/A, about 10-fold less (Foran et al, 2003;Rasetti-Escargueil et al, 2009), and that only a low toxin fraction passes through the intestinal barrier based on in vivo experiments (reviewed in Popoff and Connan, 2014), therefore justifying the amounts used in this study. We selected to use higher amounts (100 μg/intestinal loop) to more efficiently visualize the cells mediating toxin trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to BoNT/A, which has been found to enter the intestinal mucosa preferentially via crypt enteroendocrine cells (Couesnon et al, 2012), no HCcB or BoNT/B labelling was detected in epithelial crypt cells, or enteroendocrine cells using anti-chromogranin A antibodies. In vivo experiments showed that less than 0.01% to 0.1% of intraduodenally administrated BoNT can be recovered in lymph of blood circulation (reviewed in Popoff and Connan, 2014). devoid of apical brush border).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BoNT complexes containing hemagglutinins (HA) can be transported through M cells and since HAs are able to disrupt the E-cadherin intercellular junctions between intestinal epithelial cells, BoNT can pass the intestinal barrier via the paracellular pathway. In addition, BoNT free of HAs can be transported by transcytosis through certain intestinal epithelial cells (Fujinaga and Popoff, 2018;Lee et al, 2014;Matsumura et al, 2008;Matsumura et al, 2015;Popoff and Connan, 2014;Sugawara et al, 2010). Using fluorescent BoNT/A and BoNT/B or their corresponding receptor binding domains, it has been found that these molecules interact with intestinal epithelial cell surface, but with a much lower affinity than on neuronal cells.…”
Section: -5 Bonts Intestinal Barrier and Enteric Nervous Systemmentioning
confidence: 99%